TRAINING AND ASSISTANCE IN USING GEOGEBRA TO IMPROVE THE COMPETENCE OF HIGH SCHOOL MATHEMATICS TEACHERS - Darsih Idayani; Wahyu Hidayat; Selly Anastassia Amellia Kharis; Asmara Iriani Tarigan; Sumartono Sumartono (As-Sidanah, 2024)
Mathematics teachers must adapt to technological developments in the digital era. Among other problems related to learning mathematics, students tend to feel bored and uninterested in mathematics. At the same time, most teachers need help keeping up with fast technology developments. The solution offered is training and mentoring activities for using the GeoGebra software in mathematics learning in South Tangerang City in collaboration with the Subject Teacher Deliberation of Mathematics or MGMP. The material presented was about introducing GeoGebra, graphs, and function operations. Moreover, it was about solving linear programming, geometry, and calculus in GeoGebra. The pretest and posttest results showed increased participants' knowledge about GeoGebra utilization. This condition is indicated by the significance value of the t-test, which is less than 0.05 and less than 0.001. In addition, activity evaluation was carried out by filling out evaluation forms and interviews. The evaluation results show that the training and mentoring activities have enabled participants to gain new knowledge about the GeoGebra as needed in teaching mathematics in high school.